2001
DOI: 10.1007/pl00007816
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and immunology of botulinum toxin serotypes

Abstract: Botulinum toxin preparations can provide patients with a therapeutic modality that may improve both their medical condition and quality of life. The mechanism of action of the various botulinum toxin preparations and serotypes is similar: they all block neurotransmitter release. The majority of clinical conditions treated are based upon the targeted temporary chemodenervation of the selected organ. The antinociceptive effects of botulinum toxin type A (BTX-A), based on preclinical studies and clinical experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
14

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(99 citation statements)
references
References 70 publications
1
84
0
14
Order By: Relevance
“…BTX affects the nervous system through a multi-stage process that results in blocking neurotransmitter release (3,4,17). The toxin binds to the target nerve terminal through its …”
Section: Mechanism Of Action (Second Heading)mentioning
confidence: 99%
“…BTX affects the nervous system through a multi-stage process that results in blocking neurotransmitter release (3,4,17). The toxin binds to the target nerve terminal through its …”
Section: Mechanism Of Action (Second Heading)mentioning
confidence: 99%
“…По серовару возбудителя выделяют несколько типов БТ: A, B, C1, C2, D, E, F, G, H, но наиболее часто встречается тип А [6]. Заболевание (ботулизм) у человека вызывают токсины серотипов A, B, E, реже F. Для животных также токсичны серотипы С и D. …”
Section: химические характеристики и физикохимические показателиunclassified
“…The clinical effects of BoNT injections can last for 3 to 4 months [35]. In addition to BoNTs well-established inhibition of acetylcholine release at the neuromuscular junction, pre-clinical studies have shown that it is able to inhibit neuropeptide release from primary afferent nociceptive C fibers and possibly from lightly myelinated Aδ fibers [36].…”
Section: Botulinum Neurotoxinmentioning
confidence: 99%